Variants of CARD8 in Leishmania guyanensis-cutaneous leishmaniasis and influence of the variants genotypes on circulating plasma cytokines IL-1β, TNFα and IL-8. - Héctor David Graterol Sequera; Josué Lacerda de Souza; José do Espírito Santo Junior; Lener Santos da Silva; Suzana Kanawati Pinheiro; Herllon Karllos Athaydes Kerr; Mara Lúcia Gomes de Souza; Marcus Vinitius de Farias Guerra; Tirza Gabrielle Ramos de Mesquita; Rajendranath Ramasawmy (Public Library of Science (PLoS), 2023)
Nucleotide-binding oligomerization domain, leucine-rich repeat-containing protein family (NLR) are intracellular pathogen recognition receptors mediating innate immunity, releasing proinflammatory cytokines IL-1β and IL-18, and promoting pyroptotic cell death, upon sensing pathogenic or endogenous danger signals. In animal models, NLRP3 inflammasome has a dual role, pathogenic or protective in Leishmania-infection, depending on the Leishmania species and mice strain. Caspase recruitment containing domain 8 (CARD8) is a negative regulator of NLRP3 inflammasome and also an inhibitor of transcription factor NFĸB, a major transcription factor of proinflammatory cytokines. We investigated whether single nucleotide variants in CARD8 may partially explain why only a proportion of individuals coming from the same area of endemicity of leishmaniasis develop cutaneous leishmaniasis caused by Leishmania guyanensis. We genotyped four single nucleotide variants of the CARD8 gene by direct nucleotide sequencing in 1741 individuals from an endemic area of leishmaniasis, constituting 850 patients with CL and 891 healthy controls. The frequencies of the genotypes of the variants rs2288877 T>C, rs73944113 C>T, and rs2043211 A>T are similar among the patients with CL and HC, while the variant rs2288876 A>G) reveals an excess of the genotype AA among the patients with CL (44%) compared to 37% in the HC group. Allele A of the variant rs2288876 A>G) is associated with susceptibility to CL (OR = 1.2 [95%CI 1.03-1.4]; P = 0.01). Haplotype analysis showed that individuals harboring the haplotype CCAA have 280% odds of developing CL caused by L. guyanensis (OR = 3.8 [95% CI 2.0-7.7]; p = 0.00004). The variants rs2288877 T>C and rs2288876 A>G correlate with the plasma level of IL-8. Spearman correlation showed a significant positive correlation between the rs2288876 A>G allele A and the level of IL-8 (ρ = 0.22; p = 0.0002). CARD8 may partially contribute to the development of CL caused by L. guyanensis.